The processing of compound words in English: effects of word length on eye movements during reading. - Juhasz BJ (Language & Cognitive Processes, 2008)
Two experiments are reported which investigated morphological processing in English using bilexemic compound words. Long and short compound words were presented in neutral sentences and eye movements were recorded while participants read the sentences to investigate the time course of compound word recognition. In Experiment 1, the frequency of the beginning lexeme was manipulated in addition to word length while in Experiment 2 rated frequency was manipulated. These experiments represented attempts to extend Bertram and Hyona's (2003) work with Finnish compounds to English and to test the parallel dual-route model of compound processing. Predictions from this model would be that only long compound words should demonstrate a beginning lexeme frequency effect and short compound words should show an earlier effect of whole-word frequency. Contrary to this, short compound words did show a large beginning lexeme frequency effect as well as whole word frequency effects. These results will be problematic for parallel dual - route models to explain.